Mycobacterium avium subsp: Paratuberculosis sheep strains isolated from Cyprus sheep and Goats - Liapi, Maria; Botsaris, George; Slana, Iva; Moravkova, Monika; Babak, Vladimír; Avraam, Maria; Di Provvido, Andrea; Georgiadou, S.; Pavlik, Ivo (My University, 2015)
Paratuberculosis, caused by Mycobacterium avium subsp. paratuberculosis (Map), is a chronic incurable infection of intestinal tract of animals. Molecular characterization of Map isolates classifies them into two major groups, 'Cattle' or Type II and 'Sheep' or Type I/III with a different phenotype, epidemiology, virulence and pathogenesis. The aim of this study was to examine 192 Map ELISA-positive sheep and goats from Cyprus using faecal culture and genotype Map isolates using IS1311 PCR and restriction endonuclease analysis (IS1311 PCR-REA) with HinfI restriction enzyme. Map was isolated from only four (4.6%) faecal samples out of 88 sheep and 15 (14.4%) faecal samples out of 104 goats. Genotyping of the isolates using IS1311 PCR-REA revealed that sheep and goat populations on the island are infected primarily by 'Sheep' strains. Only three Map isolates from goats originated from one farm were characterized as 'Cattle' strains.
Keywords: Crohn's disease; IS1311 PCR-REA; Mycobacterium avium subsp. paratuberculosis; Cattle strain; Goat; Sheep strain